Editorial - Nain, Manjeet Singh (Indian Journal of Extension Education, 2022)
Editorial In January 2022, it was projected that the inflated prices for agricultural inputs and the demand for labour will be driving forces in 2022. Due to twin problems of low productivity and excess workforce employed in it, the per capita productivity of the workforce is very low which results in depressing the agriculture sector wages and ultimately the increased poverty. In our neighborhood, in Sri Lanka, fears of a hunger crisis are rising in, and rice production in the last harvest season had already plunged 40% to 50%. Due to the direst economic meltdown in Sri Lanka, seed and fertilizer scarcities could shrink crop yields by as much as 50%, whereas, on the other hand, Indian agricultural exports rose by about 20% to 50.21 billion during 2021-22 despite logistical challenges posed by the COVID-19 pandemic. The rise in export of agricultural and processed food products has been largely due to the various initiatives taken by the Centre Government through organizing B2B exhibitions in different countries, exploring new potential markets through product-specific and general marketing campaigns by the active involvement of Indian Embassies. The agricultural extension system needs to respond against a slowdown in growth; degradation of natural resource base; uneven and slow dissemination of technology; inefficient use of available technology and inputs and other abiotic stresses. The current issue (July- September 2022) contains 41 manuscripts dealing with issues of agriculture, dairy, fisheries, veterinary sciences, and community sciences. The various social and extension dimensions dealt with include; the role performance of agricultural input dealers including DAESI; poultry, mithun husbandry, dairy management practices, and scientific fish farming; kisan credit card; kisan mobile advisory service; soil health card; RKVY-RAFTAAR; farmer producer companies; marketing system effectiveness; migration behaviour; food adulteration; adaptation and consumption pattern during the pandemic; climate change vulnerability;, social media; the impact of mobile app; attributes of innovation for adoption; training need; job satisfaction; water management under conservation agriculture and groundwater use efficiency in irrigation; minimization of yield gap in pulses and value chains analysis; entrepreneurship development; hybrid rice; integrated pest management practices; determinants for technology socialization; effect of nutrition interventions; information and communication technology and so on. The included manuscripts were submitted from 16 Indian states and UTs covering 26 Indian institutions (SAUs/CAUs/ ATARIs/ DUs/ SVUs/ KVKs). It is reiterated that to increase the citations and wider circulation of the manuscripts published in the Indian Journal of Extension Education we need to strive hard for quality submissions. I extend my sincere thanks to all the authors for making valuable contributions. I also extend sincere thanks to all the expert members of the editorial board for their painstaking efforts. The support extended by Executive Council is duly acknowledged. Special thanks are extended to the President, ISEE; Dr. U.S. Gautam, Secretary ISEE; Dr. Rashmi Singh, Treasurer, ISEE; Dr. B. K. Singh and Joint Secretary, ISEE; Dr. J. S. Malik for providing insightful thoughts and guidance in bringing out this issue. Dr. Bhanu P. Mishra, Vice President (Central Zone) deserves special thanks for making committed efforts at all stages of ISEE matters. (Manjeet Singh Nain)